Athletes' satisfaction, intrinsic motivation and performance of archers in Malaysia - Abu Samah, Irza Hanie; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Performance in sports activities serves as a crucial indicator for ranking position among athletes. Today in Malaysia, improving athletes’ performance and ensuring continuity of athletes is pertinent for the national sport development in realizing the potential among citizens who have passion for sports. This study examines relationships between athletes’ satisfaction and intrinsic motivation as contributor to athletes’ performance. A total of 139 questionnaires were administered among participants in the National Open Competition in Universiti Putra Malaysia (UPM) and Universiti Utara Malaysia (UUM). Data were analyzing using SPSS version 19.0. The results revealed that, majority of the participants have low performance of 57.5 percent. Also, some athletes have moderate performance of 43.2 percent; while athletes with high performance were only 2.30 percent. The Pearson correlation analysis shows there is no significant relationship on athletes’ satisfaction and intrinsic motivation with performance (p>0.001). The study further recommend among others, there should be more support for the athletes that are involving in archery games in order to bring the best out of them which will trigger high performance in them both at the national and international level.